2014
DOI: 10.1117/1.oe.53.12.122509
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced damage of optical thin films submitted to 343, 515, and 1030 nm multiple subpicosecond pulses

Abstract: Laser-induced damage of optical thin films submitted to 343, 515, and 1030 nm multiple subpicosecond pulses Dam-Bé Douti Laurent Gallais Mireille Commandré Downloaded From: http://opticalengineering.spiedigitallibrary.org/ on 05/15/2015 Terms of Use: http://spiedl.org/termsLaser-induced damage of optical thin films submitted to 343, 515, and 1030 nm multiple subpicosecond pulses Abstract. Optical materials submitted to multiple subpicosecond irradiations are known to exhibit a decrease of the laser-induced dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Overall, it has been demonstrated that the laser damage resistance of an optic in the subpicosecond regime is both limited by its intrinsic properties (linked to its electronic structure) [7,8] and by the presence of embedded defects induced by the manufacturing process [4,9]. The densities of such embedded defects can be as high as two hundreds of defects∕cm 2 , estimated from the measurement of damage densities during rasterscan tests [10]. The questions we wanted to answer in this Letter are: Once a damage site is initiated, what is its growth probability?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it has been demonstrated that the laser damage resistance of an optic in the subpicosecond regime is both limited by its intrinsic properties (linked to its electronic structure) [7,8] and by the presence of embedded defects induced by the manufacturing process [4,9]. The densities of such embedded defects can be as high as two hundreds of defects∕cm 2 , estimated from the measurement of damage densities during rasterscan tests [10]. The questions we wanted to answer in this Letter are: Once a damage site is initiated, what is its growth probability?…”
mentioning
confidence: 99%
“…In this context, many studies have been carried out to better understand laser damage resistance of optical components. In the case of subpicosecond laser systems, the effect of irradiation conditions (fluence, pulse duration, wavelength, number of pulses, and environment) [1][2][3][4], design and manufacturing conditions (coating process, materials, electric-field distribution) [5,6] were thoroughly studied. Overall, it has been demonstrated that the laser damage resistance of an optic in the subpicosecond regime is both limited by its intrinsic properties (linked to its electronic structure) [7,8] and by the presence of embedded defects induced by the manufacturing process [4,9].…”
mentioning
confidence: 99%
“…This ratio is calculated numerically based on the refractive index and film thickness deduced from spectrophotometric measurements. Band gap (eV) Band gap (eV) 8 …”
Section: Methodsmentioning
confidence: 99%
“…We observe a decrease of the LIDT with the number of applied pulses that corresponds to a drop of more than 20% of the threshold in the first 100 pulses, as observed in other works with similar irradiation conditions. 12,13 This behavior was attributed to the high densities of deep and shallow traps, i.e. electronic states in the forbidden band that can trap the conduction band electrons after a subthreshold irradiation.…”
Section: Hafnia Single Layersmentioning
confidence: 97%